2016
DOI: 10.1016/j.acap.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Do On-Site Mental Health Professionals Change Pediatricians' Responses to Children's Mental Health Problems?

Abstract: Objective The objectives were to: assess the availability of on-site mental health professionals (MHP) in primary care; examine practice/pediatrician characteristics associated with on-site MHPs; and determine whether presence of on-site MHPs is related to pediatricians’ co-managing or more frequently identifying, treat/managing or referring MH problems. Methods Analyses included AAP members who participated in an AAP Periodic Survey in 2013 and who practiced general pediatrics (N=321). Measures included soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…The findings of this survey may not be generalizable to family practitioners, nurse practitioners, or pediatricians that are not AAP members. However, response rates were consistent with other recent national surveys of physicians, 21,22 and the methodology was robust, including the use of response rate weights to account for non-response bias. 23 Furthermore, data from the American Board of Pediatrics estimates 61% of US boardcertified pediatricians ages 27 to 70 years are AAP members, suggesting AAP members do represent the majority of boardcertified pediatricians.…”
Section: Discussionsupporting
confidence: 78%
“…The findings of this survey may not be generalizable to family practitioners, nurse practitioners, or pediatricians that are not AAP members. However, response rates were consistent with other recent national surveys of physicians, 21,22 and the methodology was robust, including the use of response rate weights to account for non-response bias. 23 Furthermore, data from the American Board of Pediatrics estimates 61% of US boardcertified pediatricians ages 27 to 70 years are AAP members, suggesting AAP members do represent the majority of boardcertified pediatricians.…”
Section: Discussionsupporting
confidence: 78%
“…However, the majority of pediatricians are still not managing or co-managing most common child MHCs. 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…21 However, our prior study demonstrated that only a third of pediatricians reported co-managing at least half of their patients. 4 Co-management for MH care is understudied and we know little about what factors influence pediatricians to co-manage MHCs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations